2013
DOI: 10.1186/2050-6511-14-52
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and pharmacokinetic effects of oral 1,3-dimethylamylamine administration in men

Abstract: Background1,3-dimethylamylamine (DMAA) has been a component of dietary supplements and is also used within "party pills," often in conjunction with alcohol and other drugs. Ingestion of higher than recommended doses results in untoward effects including cerebral hemorrhage. To our knowledge, no studies have been conducted to determine both the pharmacokinetic profile and physiologic responses of DMAA.MethodsEight men reported to the lab in the morning following an overnight fast and received a single 25 mg ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 11 publications
1
32
0
Order By: Relevance
“…Recreational doses appeared to adhere to recommended sports dosage (25-75 mg) with users aware of negative adverse effects on consumption of over 100 mg. Similar to Schilling et al (2013), DMAA with caffeine as attractive as 'daily pick me up'.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Recreational doses appeared to adhere to recommended sports dosage (25-75 mg) with users aware of negative adverse effects on consumption of over 100 mg. Similar to Schilling et al (2013), DMAA with caffeine as attractive as 'daily pick me up'.…”
Section: Discussionmentioning
confidence: 90%
“…Recommended single 25 mg doses of DMAA are reported to incur no significant untoward effect on blood pressure, resting heart rate or body temperature (Schilling, Hammond, Bloomer, Presley, & Yates, 2013). Sport supplements typically contain doses of 25-65 mg (Venhuis & de Kaste, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…453 DMAA is a component of "party pills," often in conjunction with alcohol and other drugs, that results in cerebral hemorrhage when ingested. 454 On April 27, 2012, the FDA sent warning letters to 10 manufacturers of 16 products containing DMAA. The warning indicated that the products were considered adulterated because DMAA is considered a NDI.…”
Section: Example Of Dimethylamylaminementioning
confidence: 99%
“…Further, glycerol is listed among the masking agents as a compound potentially affecting the plasma volume. [128][129][130][131] Since health issues [132] as well as deaths [133] were put into context with DMAA (ab)use, studies on its pharmacokinetics [134] and the detection of this compound in doping control as well as nutritional supplements [135] has become a priority in different fields of analytical chemistry. [126,127] Stimulants Within the class of stimulating agents, particularly methylhexaneamine (1,3-dimethylamylamine, DMAA) has been subject of much discussion and research recently, mostly concerning the question as to its natural or non-natural origin and the more than 300 AAFs as recorded in 2012.…”
Section: Diuretics and Other Masking Agents And Stimulants Diuretics mentioning
confidence: 99%